Academic Collaboration Of Rawalpindi Medical University & Al-Azhar University For Gaza Students: A Ray Of Hope In A Catastrophic Scenario - Shahid, Rizwana; Riaz, Mehwish; Asif, Omaima; Umar, Muhammad; Bilal, Sana (Journal of Rawalpindi Medical College, 2025)
Objective: To review the academic collaboration between Rawalpindi Medical University and Al-Azhar University of Gaza for assisting undergraduates of Gaza. Methods: A cross-sectional descriptive survey was carried out to review academic collaboration of RMU with Al-Azhar University of Gaza that was primarily meant to endow educational facilitation to Palestinian medical students during their country-wide crisis. Of the 36 Palestinian medical students enrolling at RMU for continuation of medical education, 29 underwent an objective assessment of their prior knowledge. Following the assessment of prior knowledge by the shared Table of Specifications (TOS), a composite curriculum designed by the competent faculty of RMU was implemented. Results: Of the 36 medical students coming from the Gaza Strip to RMU, 29 students underwent subject-wise objective assessment before implementation of the purpose-built curriculum. They attempted C2, C3 level one best Multiple-Choice Questions (MCQs) of Anatomy, Physiology, Biochemistry, Pharmacology and Pathology. Each section consisted of 10 MCQs. The students achieved the highest mean score in Pathology (5.52 ± 2.05). The mean score of the students in Physiology (3 ± 1.4) was the lowest. The comprehensive curriculum with a detailed plan of assessment, learning outcomes, teaching methods and Continuous Internal Assessment (CIA) weightage was also disseminated. A mentoring team was also familiarised with guidance. A thorough monitoring system was also introduced for the smooth execution of the whole process. Conclusion: The academic collaboration between RMU and Al-Azhar University of Gaza would be useful to Palestinian medical students in completing their medical education. Keywords: academic collaboration, Gaza Strip, medical students, purpose-built curriculum